Child support policy: An international perspective (Chapter 1) - C. Skinner; J. Bradshaw; J. Davidson (Luxembourg Income Study (LIS), 2008)
This is a chapter from a report of a comparative study of child support policy in fourteen countries (Skinner, C., Bradshaw, J. and Davidson, J. (2007) Child support policy: an international perspective, Department for Work and Pensions Research Report 405, Leeds: Corporate Document Services. www.dwp.gov.uk/asd/asd5/rports2007-2008/rrep405.pdf. The chapter is an analysis of LIS data for twelve of these countries and explores the contribution of child support to the reduction in child poverty. The LIS analysis compares the prevalence and characteristics of lone parents, explores the proportion of families with children receiving child maintenance, and the contribution that it made to their income and the reduction of child poverty circa 2000. Child maintenance made a comparatively small contribution to the relief of child poverty overall, but if lone parents actually received child maintenance the poverty reduction achieved was much more significant. The impact of child maintenance also varied according to whether the lone parent was or was not in employment. For lone parents in employment in the UK, child maintenance could reduce child poverty by over two-thirds - more than any other country except Austria, France and the Netherlands. However, it was not more effective overall because comparatively few non-widowed lone parents had employment and child maintenance in the UK. See also Bradshaw, J. (2006) Child support and child Poverty, Benefits: The Journal of Poverty and Social Justice, October, 14, 3, 199-208.
Keywords: 330; Sozialstaat; Sozialpolitik; Familienpolitik; Alleinerziehende; Arbeitsangebot; Kinder; Kinderbetreuung; OECD-Staaten